Community activities, civil organisations, and their role in the village of Átány - Gerencsér, Ilona; Bálint, Csaba (ACTA REGIONIS RURUM, 2023)
The study describes the local society of Átány and the characteristics of local social coexistence. The main themes of the study are related to the local people's own community, the developments in their municipality and community life. It also presents the opinions of the people of Átány about their civil society organisations and their level of awareness of these organisations. Information for the study was obtained through documentary analysis, a publicly available database, a questionnaire survey of the population, and interviews with people familiar with community life.
Keywords: village survey; Átány; local society; community life